Investigating the benefits and harms of hypodermoclysis of patients in palliative care: A consecutive cohort study. (May 2022) - Agar, Meera R; Chang, Sungwon; Amgarth-Duff, Ingrid; Garcia, Maja V; Hunt, Jane; Phillips, Jane L; Sinnarajah, Aynharan; Fainsinger, Robin
Background: Palliative populations are at risk for dehydration which can cause discomfort, distress and cognitive symptoms. Subcutaneous hydration ('hypodermoclysis') has been used as an alternative administration route to the more invasive intravenous route, but research is lacking on its net clinical effects (harms and benefits) for palliative populations, particularly in real world settings. Aim: To quantify prospectively the net clinical effects of hypodermoclysis in palliative patients with advanced disease who required supplementary fluids. Design: Multisite, multinational consecutive cohort study. Setting/participants: Patients receiving hypodermoclysis in an inpatient palliative care setting. Results: Twenty sites contributed data for 99 patients, of which 88 had complete benefits and harms data. The most common primary target symptom for infusion was generalised weakness (18.2%), and the most common non-symptom indication was supplemental hydration (31.8%). Benefits were experienced in 33% of patients in their primary target symptom, and in any symptom in 56.8%. Harms were experienced in 38.7% of patients (42% at Grade 1). Benefits increased with higher performance status, while harms were more frequent in patients with lower performance status (Australia-modified Karnofsky performance status ⩽40). Patients in the terminal phase of their illness experienced the least benefit (15.4% in any indication only) and had more frequent harms (38%). Conclusions: Hypodermoclysis may improve certain symptoms in patients in palliative care but frequency of harms and benefits may differ at certain timepoints in the illness trajectory. Further research is needed to better delineate which patients will derive the most net clinical benefit from hypodermoclysis.